Aspek Bunyi dan Imaji Puisi Balada Karya Rendra dan Implikasinya bagi Pembelajaran Sastra di SMU Jurusan Bahasa - Anneke Sumarauw Pangkerego (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This research studied sound and imagination aspects in Balada Orang-Orang Tercinta by Rendra and its learning implication for language program in high schools. The study used descriptive research design and data were analyzed using content analysis. The result showed that there were 566 sound aspects which included 37 aliteration, 55 assonantion, 211 ephony, 208 cacophony , 35 anaphor, and no onomatopoeiac aspect was found. Dealing with imagination aspects, there were 485 aspects with various frequency of appereance, which included 208 aspects related to sight, 82 to hearing, 43 to feeling, 17 to taste, 7 to smell, and 128 to physical movements. This finding showed the necessity to focus attention when learning how to analyze poems.